Evaluation of respiratory muscle strength in individuals having Down syndrome - Furlan, Fernanda Roseane; Sgariboldi, Dayla; Brigatto, Patrícia; Pazzianotto- Forti, Eli Maria (O Mundo da Saúde, 2015)
As a result of muscle changes caused by the generalized hypotonia found in individuals with Down syndrome (DS), these subjects develop changes in respiratory muscle strength. The objective of the study was to assess respiratory muscle strength (RMS) of individuals having DS. Thus, the objective of the study was to evaluate the respiratory muscle strength (RMS) in individuals with DS. It was cross-sectional study, conducted at the Association of Parents and Friends of Exceptional (APFE) of countryside of São Paulo. 20 volunteers were evaluated, divided into two groups, 10 non-syndromic individuals and 10 individuals diagnosed with DS, aged between 18 and 35 years, of both genders. The evaluation of RMS was performed by an analog manometer through which were measured maximal inspiratory pressures (MIP) and maximum expiratory pressures (MEP). For data analysis, were used the BioEstat version 5.3. Data normality was verified by the Shapiro-Wilk test. After, comparison tests were used for two independent samples (Student’s t and Mann-Whitney tests), adopting a significance level of 5%. When comparing both groups, we can find a significant difference in MIP (p= 0.0011) and MEP (p= 0.0002), and lower RMS values were obtained in the group of individuals with DS. SD (MIP: -109±49.49 x -29.50±9.07) and (MEP: 127±44.06 x 45.50±10.11) Therefore, individuals with Down syndrome have decreased RMS. It is believed that these individuals would benefit from a rehabilitation program, including physiotherapy, thus minimizing possible respira- tory complications.